An Atraumatic Femoral Fracture in a Patient with Rheumatoid Arthritis and Osteoporosis Treated with Denosumab. (5th December 2013) - Villiers, J.; Clark, D. W.; Jeswani, T.; Webster, S.; Hepburn, A. L.
Abstract : Osteoporosis is responsible for a significant burden both individually and socially, but is readily treated with antiresorptive agents and mineral supplementation. However, long-term usage of these agents, notably bisphosphonates, is rarely associated with atypical fractures. Denosumab is a monoclonal antibody that reduces osteoclast activity and thus increases bone mineral density. In this case report, we present a 78-year-old woman with a background of rheumatoid arthritis and osteoporosis who presented with an atypical diaphyseal femoral fracture.